2002
DOI: 10.1136/ip.8.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Recording of community violence by medical and police services: Figure 1

Abstract: Objectives: To determine the extent to which community violence that results in injury treated in emergency departments appears in official police records and to identify age/gender groups at particular risk of under-recording by the police. Methods: Non-confidential data for patients with assault related injury treated in the emergency departments of two hospitals in one South Wales city (Swansea) during a six month period were compared with data relating to all recorded crimes in the category "Violence again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 5 publications
1
35
0
Order By: Relevance
“…Carlton (HVIP co-director) suggested that one approach could compare the data collected by the hospital to data collected by the police. This strategy parallels the procedures implemented in the UK 13 :…”
Section: Logisticalmentioning
confidence: 99%
See 3 more Smart Citations
“…Carlton (HVIP co-director) suggested that one approach could compare the data collected by the hospital to data collected by the police. This strategy parallels the procedures implemented in the UK 13 :…”
Section: Logisticalmentioning
confidence: 99%
“…13 For example, low rates of police recording intimate partner violence have prompted legislation in some states to make reporting by health professionals' mandatory. 18 Although most states require medical personnel to report all nonfatal shootings to law enforcement, the rate of compliance is unknown.…”
Section: Death In Custody Reporting Actmentioning
confidence: 99%
See 2 more Smart Citations
“…These data have shown that 75-80% of assaults resulting in hospital treatment do not appear in police records, and also that police recording varies by patient age, gender and violence location. Violence resulting in treatment of older women, for example, is more likely to appear in police records than that affecting young men (Sutherland et al, 2002). A principal reason for non-recording of violence by the police is lack of reporting.…”
Section: Measuring Violencementioning
confidence: 99%